Developing a research and restoration plan for Arctic-Yukon-Kuskokwim (western Alaska) salmon (National Academies Press, 2005)
Recent declines in the abundance of salmon in the Arctic-Yukon-Kuskokwim (AYK) region of western Alaska have created hardships for the people and communities who depend on this resource. In 2002, the AYK Sustainable Salmon Initiative (SSI) was created to undertake research to understand the reasons for this decline and to help support sustainable management in the region. This report makes recommendations for developing the research that the AYK SSI science plan should be based on, and relates the development of a restoration plan to the results of that research.